EFEKTIVITAS STUDENT TEAMS ACHIEVEMENT DIVISION DITINJAU DARI PRESTASI BELAJAR MATEMATIKA - Adinda Vrihastien; Sri Adi Widodo; Annis Deshinta Ayuningtyas (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
This study aims to determine the effectiveness of the Student Teams Achievement Division cooperative learning model in terms of mathematics achievement. This type of research is an experimental study with a population of eighth grade students of SMP N 3 Bantul taken using cluster random sampling technique. research instruments use tests on the subject matter of opportunity. data analysis techniques using t-test by considering the assumption test for the test. From the results of the study it can be concluded that on learning achievement, the Student Teams Achievement Division model is more effectively used in learning mathematics in the material opportunities when compared with the direct learning model. related to this result, the Student Teams Achievement Division Model can be used as an alternative in learning mathematics, especially in the material opportunities.